Evaluation of Four Point‐Of‐Care Glucose Meters in Alpacas. (4th June 2013) - Beemer, O.; Byers, S.; Bohn, A.
<x xml:space="preserve">Abstract</x> Purpose Hospitalized alpacas are often hyperglycemic requiring frequent blood glucose testing. Objectives To compare the performance of 4 brands of glucometers with a laboratory‐based analyzer (LCA) over a range of glucose concentrations in alpacas. Animals Four healthy male alpacas. Methods A 2‐treatment cross‐over study was utilized. The alpacas were given 0.4 U/kg of regular insulin intravenously and then 500 mg/kg of dextrose intravenously with a 1 week washout period between treatments. Blood samples were collected from 10 minutes before until 6 hours after drug administration. Glucose concentrations were measured in whole blood and plasma samples on 4 glucometers, and serum glucose was measured on an LCA. Results Glucometer performance varied depending on whether glucose concentrations were measured in plasma or whole blood. Based on error grid analysis, the Precision Xtra and One Touch Ultra 2 glucometers were clinically acceptable for testing whole blood samples, whereas the Accu‐Chek Aviva and Nova StatStrip Xpress glucometers were clinically acceptable for testing plasma samples in comparison with serum glucose concentrations determined by the LCA. All glucometers had systematic and proportional biases that varied based on sample type. Conclusions and Clinical Importance Human‐based glucometers in alpacas should be used cautiously, particularly at higher blood glucose concentrations. The blood sample type (plasma or whole blood) can alter meter performance when compared with serum glucose concentrations and potentially lead to errors in clinical decisions.